2022
DOI: 10.1093/burnst/tkac039
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical characteristics of burns in mainland China from 2009 to 2018

Abstract: Background Burn injuries place a heavy burden on the global healthcare system. However, there is still a lack of nationwide studies on the epidemiological characteristics of burn patients in mainland China. The present study aims to accurately analyze the clinical characteristics of burn patients by collecting data in mainland China from 2009 to 2018, which will provide effective strategies for healthcare systems and the government in mainland China. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
6
2
Order By: Relevance
“…Previous studies showed that summer was the season when burns and scalds were more likely to occur, 16,43 but our results…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Previous studies showed that summer was the season when burns and scalds were more likely to occur, 16,43 but our results…”
Section: Discussioncontrasting
confidence: 82%
“…patients in mainland China, burn patients under 10 years of age account for the highest proportion of total burn patients. 16 The trend of US pediatric burn hospitalizations from 2003 to 2016 showed that although the rate of burn hospital admission in the US has decreased considerably, the proportion of burn admissions among children aged 1-4 years increased by 9.1% and among children aged 5-9 years by 9.9%. 17 Two other studies of the epidemiology of burns in children at the University of Zurich Children's Hospital in Switzerland suggest that burns in children are mainly associated with kitchen supplies, hot tea, and coffee, and 65% of children have received different forms of first aid before hospitalization.…”
mentioning
confidence: 99%
“…This retrospective study analyzed the epidemiological data and clinical outcomes of burn patients aged 18 years and above who were admitted to our burn center during the period 2017-2022. The number of adult burn patients decreased annually over the six-year period, in accordance with global trends in burn incidence (1,(11)(12)(13). Suzhou is one of the more economically developed regions in China.…”
Section: Discussionmentioning
confidence: 65%
“…Burns are the leading cause of morbidity and mortality around the world, with devastating economic and social impacts, particularly in developing countries 1–5 . The World Health Organization (WHO) reports that burns are responsible for more than 300 000 deaths worldwide each year 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Burns are the leading cause of morbidity and mortality around the world, with devastating economic and social impacts, particularly in developing countries. 1 , 2 , 3 , 4 , 5 The World Health Organization (WHO) reports that burns are responsible for more than 300 000 deaths worldwide each year. 6 Despite advances in treatment methods such as fluid resuscitation, early enteral nutrition, and aggressive surgery, burns remain a leading cause of mortality.…”
Section: Introductionmentioning
confidence: 99%